Two-stage excision of type III sacrococcygeal teratoma with massive abdominal extension in a 3-month-old girl: A case report with brief literaturereview - Ghritlaharey, Rajendra K (Indian Journal of Child Health, 2024)
Sacrococcygeal teratomas (SCTs) are the most common germ cell tumor in neonates occurring in approximately 1 in 30,000 to 40,000 births. Here in reporting a 3-month-old girl presented with rapid distension of the abdomen and a tumor-like growth at her right gluteal area, since birth. She also had features suggestive of intestinal obstruction. Clinical examination revealed marked distension of the abdomen, although it was soft and features suggestive of ascites. Visible bowel loops were also detected, suggesting intestinal obstruction. Her perineal/right gluteal examination revealed a soft-to-firm tumor. Her clinical and radiological investigations (ultrasonography and magnetic resonance imaging scan of the abdomen, pelvis, and perineal area) were suggestive of SCT. Abdominal exploration was carried out on an emergency basis for intestinal obstruction, and the cystic tumor was partially excised. After a few days, the remaining pelvic and perineal parts of the tumor were completely excised through posterior, sagittal incision. Her post-operative recovery was uneventful, and she was discharged in good condition. Her resected specimens were subjected to histology and were reported as mature teratoma, without any evidence of malignancy. She was doing well, without a recurrence, in a follow-up done 2 year after the surgical procedures.